2021
DOI: 10.1002/alz.12394
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial ROS control neuronal excitability and cell fate in frontotemporal dementia

Abstract: Introduction The second most common form of early‐onset dementia—frontotemporal dementia (FTD)—is often characterized by the aggregation of the microtubule‐associated protein tau. Here we studied the mechanism of tau‐induced neuronal dysfunction in neurons with the FTD‐related 10+16 MAPT mutation. Methods Live imaging, electrophysiology, and redox proteomics were used in 10+16 induced pluripotent stem cell‐derived neurons and a model of tau spreading in primary cultures. Results Overproduction of mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 79 publications
(154 reference statements)
1
47
1
Order By: Relevance
“…Similarly, redox proteomics is rapidly emerging in oxidative stress research as it can identify Spin traps and spin probes used for electron-spin resonance assays have high selectivity and specificity and are among the essential tools in oxidative stress research. Similarly, redox proteomics is rapidly emerging in oxidative stress research as it can identify ROS targets and modifications induced [49][50][51]. However, low throughput and expensive instruments requiring a high level of expertise reduce their applicability.…”
Section: Cellular-based Antioxidant Assaysmentioning
confidence: 99%
“…Similarly, redox proteomics is rapidly emerging in oxidative stress research as it can identify Spin traps and spin probes used for electron-spin resonance assays have high selectivity and specificity and are among the essential tools in oxidative stress research. Similarly, redox proteomics is rapidly emerging in oxidative stress research as it can identify ROS targets and modifications induced [49][50][51]. However, low throughput and expensive instruments requiring a high level of expertise reduce their applicability.…”
Section: Cellular-based Antioxidant Assaysmentioning
confidence: 99%
“…Additional studies demonstrated altered mitochondrial function in iPSC-derived neurons from patients with the 10 + 16 mutation (Esteras et al, 2017(Esteras et al, , 2021. 10 + 16 neurons carried an increased mitochondrial membrane potential leading to overproduction of cytosolic and mitochondrial reactive oxygen species (ROS).…”
Section: Frontotemporal Lobar Degeneration Withmentioning
confidence: 99%
“…10 + 16 neurons exhibited a depolarized AP threshold, a reduced amplitude and altered shape of the induced AP spike and the need for an almost two-fold stronger current that was needed to trigger neurons to fire an AP ( Kopach et al, 2020 ). Furthermore, 10 + 16 patient-derived cortical neurons showed increased expression of AMPA and NMDA receptors containing GluA1 and NR2B subunits leading to altered glutamatergic signaling, calcium overload and excitotoxicity ( Esteras et al, 2021 ). The application of mitochondrial antioxidants MitoQ and MitoTEMPO to the cell culture media led to recovery of impaired Ca ++ signaling and to prevention of cell death ( Esteras et al, 2021 ) as described for MitoQ before ( Esteras et al, 2017 ).…”
Section: Human Induced Pluripotent Stem Cell Models Of Frontotemporal Lobar Degeneration With Tau Pathologymentioning
confidence: 99%
See 2 more Smart Citations